5x-3(x-2)=0

Simple and best practice solution for 5x-3(x-2)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-3(x-2)=0 equation:


Simplifying
5x + -3(x + -2) = 0

Reorder the terms:
5x + -3(-2 + x) = 0
5x + (-2 * -3 + x * -3) = 0
5x + (6 + -3x) = 0

Reorder the terms:
6 + 5x + -3x = 0

Combine like terms: 5x + -3x = 2x
6 + 2x = 0

Solving
6 + 2x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 2x = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 2x = 0 + -6
2x = 0 + -6

Combine like terms: 0 + -6 = -6
2x = -6

Divide each side by '2'.
x = -3

Simplifying
x = -3

See similar equations:

| 2+7x=-28+x | | -6+12=-60 | | x-3(x-1)=-9 | | 2x-4(x-3)=x-6 | | 9+10(2)=x | | 15x+7=-3x+25 | | x*y=21 | | Y-20+10=70 | | x^2=x*-1 | | 23x=x | | 20y+20=70 | | 20y+10=80 | | sin(2z+i)=2cos(2z+i) | | 64+64+64+64+64+64+64+64+64= | | ex=1 | | 48m-28m+12m= | | (x-2)+1+3x=5(x+1) | | 16x^2+24x+9=6 | | 12x+12=5x+96 | | 79-5x=13x+21 | | 5(x+1)-6x=3x-9 | | c-5c+7c= | | cos(x)+2x=0 | | 4x-1×(0.5)3-2x=1/8-x | | x*x+2x-23.333=0 | | 12+9x=6x | | 0.65=0.3+0.7x | | 5(x/6-x/2)-7(x/2-x/4)=9 | | 5(x/6-x/2)-80 | | x:2x+9=6 | | 30(a*a*a)*2(a*a*a*a)=1 | | (5x+3y)=360 |

Equations solver categories